A biomimetic 3D microtubule-orientated poly(lactide-co-glycolide) scaffold with interconnected pores for tissue engineering. Issue 21 (7th June 2015) - Shen, Hong; Niu, Yuguang; Hu, Xixue; Yang, Fei; Wang, Shenguo; Wu, Decheng
<x xml:space="preserve">Abstract</x> We constructed microtubule-orientated PLGA scaffolds with interconnected pores by an improved thermal-induced phase separation technique using a mixed solvent of 1, 4-dioxane and water.